Temps et usage du temps par les entrepreneurs algériens - Mohamed Madoui (Temporalités)
Based on a qualitative investigation begun in 2002 in Kabylia (Algeria), this article aims to analyze how Algerian entrepreneurs manage time, while the country undergoes a transition from a planned to a market economy with all that this change implies in the way of transforming attitudes and the social behavior of individuals with respect to labor as well as with regard to time. The thirty Small and Middle-sized Businesses surveyed show that the small Algerian firm is confronted with temporality conflicts between the rythms of industrial production and the religious prescriptions, with the result that real negotiations have got under way between employer and employees.